Radiographs demonstrate poor accuracy for evaluation of postoperative osseous integration of osteochondral allografts in the knee - Navya Dandu; Tristan Elias; Erik Haneberg; Andrew Phillips; Corey M. Beals; Christopher M. Brusalis; Daniel Kaplan; Nicholas A. Trasolini; Mario Hevesi; Brian J. Cole; Adam B. Yanke (Elsevier, 2024)
ABSTRACT: Introduction: This study evaluates the inter-rater reliability and accuracy of radiographs in assessing healing of osteochondral allografts (OCA) in the knee compared with computed tomography (CT) imaging is currently unknown. Methods: A retrospective review patients who underwent OCA transplantation with postoperative knee radiographs obtained at three and six months, and CT scans obtained at six months was conducted. Three board-eligible orthopaedic surgeons independently graded postoperative radiographs, utilizing the grading scale established by Oladeji et al (2017), and the CT scans utilizing the grading scale established by Gelber et al (2021). Their consensus measurements served as a comparative gold standard. Results: Among 44 prospectively imaged grafts, 13 (29.5%) had radiographs at three months and 28 (63.6%) had radiographs available for evaluation at six months. Assessment of radiographic integration demonstrated low reliability (Intraclass correlation coefficient (ICC): -0.02 to 0.14). On CT scan, this improved to fair reliability (κ = 0.29, P < .001). However, Spearman rho between CT and x-ray (XR) grading demonstrated poor correlation (ρ = −0.23, P = .04). Among six-month postoperative radiographs, accuracy of cyst identification was negatively correlated to greater degree of cystic changes from 90.9% (30/33 correct; no cystic changes) to 19.4% (7/36 correct; small cystic changes) and 33.3% (5/15 correct; large cystic changes). Overall true positive cyst detection rates on radiographs were 27.8% to 46.7%. Conclusions: Radiographs demonstrate poor inter-rater reliability and accuracy in evaluation of healing after OCA transplantation of the knee. There was a high rate of missed cystic changes on radiographic analysis and poor correlation with CT scan findings.